2017
DOI: 10.1158/0008-5472.can-17-1066
|View full text |Cite
|
Sign up to set email alerts
|

Localized Synchrotron Irradiation of Mouse Skin Induces Persistent Systemic Genotoxic and Immune Responses

Abstract: The importance of nontargeted (systemic) effects of ionizing radiation is attracting increasing attention. Exploiting synchrotron radiation generated by the Imaging and Medical Beamline at the Australian Synchrotron, we studied radiation-induced nontargeted effects in C57BL/6 mice. Mice were locally irradiated with a synchrotron X-ray broad beam and a multiplanar microbeam radiotherapy beam. To assess the influence of the beam configurations and variations in peak dose and irradiated area in the response of no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 49 publications
0
36
0
2
Order By: Relevance
“…In a similar manner, free radicals have a bivalent nature in IC; excess levels of ROS cause tissue damage, whereas small amounts protect cellular functions 50 . To this end, the IRI biology is highly reminiscent of the complexities in radiation-induced bystander/distant effect biology 34 . Within this frame, a systemic response has been depicted in out-of-field tissues upon irradiation verified by γH2AX foci suggesting DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar manner, free radicals have a bivalent nature in IC; excess levels of ROS cause tissue damage, whereas small amounts protect cellular functions 50 . To this end, the IRI biology is highly reminiscent of the complexities in radiation-induced bystander/distant effect biology 34 . Within this frame, a systemic response has been depicted in out-of-field tissues upon irradiation verified by γH2AX foci suggesting DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Within this frame, a systemic response has been depicted in out-of-field tissues upon irradiation verified by γH2AX foci suggesting DNA damage. A hint for the underlying mechanism comes from the elevated circulating levels of certain cytokines including TGF-β1, which may play a role as mediators of non-targeted effects by promoting oxidative DNA damage at distant sites 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses up to 0.1 Gy can be acquired during medical-diagnostic procedures employing radiation exposure (i.e., whole-body CT scans, positron-emission tomography, or interventional radiology). Although local- or partial-body irradiation is generally used in clinical situations, it has been shown by Ventura et al that even local irradiation can elicit systemic immune responses and can modulate DC function at systemic level [49]. …”
Section: Discussionmentioning
confidence: 99%
“…The defined geometry and coherence of the synchrotron beam delivers IR to small volumes with lower scatter, and the high dose rate (up to >1,000 Gy/sec) minimizes motion artifacts, but also introduces the "FLASH" effect (Durante et al, 2018). Ventura et al (2017) reported that that various synchrotron settings (IR dose, volume, beam modality) trigger similar systemic effects in normal mouse tissues of wild-type C57BL/6 mice. Depending on the level of scatter radiation (Lobachevsky et al, 2015b), these effects were attributed to either true abscopal signaling, or to direct low-dose scatter radiation.…”
Section: Improving the Mechanistic Understanding Of Systemic Propagatmentioning
confidence: 99%